2014
DOI: 10.1016/j.ijfatigue.2013.04.012
|View full text |Cite
|
Sign up to set email alerts
|

About the effect of plastic dissipation in heat at the crack tip on the stress intensity factor under cyclic loading

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible. AbstractBecause of the reverse cyclic plastic zone at the crack tip, there is plastic dissipation in heat at the crack tip under cyclic loading. That creates a heterogeneous temperature field around the crack tip. A thermo-mechanical model is proposed in this paper for evaluating the consequence of this temperature field on the Mode I stress intensity factor. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 9 publications
0
23
0
Order By: Relevance
“…Internal friction produced within a material during cyclic loading results in the generation of several energy forms including elastic strain energy, plastic strain energy, and inelasticity and heat generation and dissipation [2][3][4]. Ultrasonic experiments have demonstrated that energy generation and dissipation in the VHCF regime results in an increase of temperature of the test specimen.…”
Section: Introductionmentioning
confidence: 99%
“…Internal friction produced within a material during cyclic loading results in the generation of several energy forms including elastic strain energy, plastic strain energy, and inelasticity and heat generation and dissipation [2][3][4]. Ultrasonic experiments have demonstrated that energy generation and dissipation in the VHCF regime results in an increase of temperature of the test specimen.…”
Section: Introductionmentioning
confidence: 99%
“…and Louche, 2000). A second way is to use the full temperature field to evaluate the heterogeneous mechanical field, under the hypothesis of thermo-elasticity (Bodelot et al, 2009), adiabaticity (Kapoor and Nemat-Nasser, 1998) or by a comparison to finite element computation (Ranc et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The second main approach used to evaluate the heat sources is to perform an ''inverse'' analysis where the distribution of the heat sources is assumed and the magnitude is adjusted from the comparison between experimental and computed thermal fields on the basis of an analytical or a finite elements simulation (Ranc et al, 2014;Le Saux et al, 2013). This second option remains difficult for numerous reasons: the thermomechanical problem is usually ill posed and can lead to several solutions, the thermal exchange conditions are difficult to evaluate, especially when large displacements occur and the conversion of mechanical energy into dissipated energy is often complex with numerous parameters.…”
Section: Introductionmentioning
confidence: 99%
“…This K pc was proposed as a new mechanical driving force parameter for predicting FCG rate, able to explain important phenomena associated with the plastic zone around a fatigue crack tip, such as the effects of load ratio R, single overload and the FCG behavior under cyclic compression. Ranc et al [20] quantified the effect of heterogeneous temperature on stress intensity factor. The energy dissipated in the cyclic plastic zone ahead of crack tip produces thermal expansion of the material which affects the stress field.…”
Section: Introductionmentioning
confidence: 99%